2019
DOI: 10.1590/0103-6440201902329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conditioning Protocols and Ultrasonic Application of an Infiltrant Resin in White Spot Lesions

Abstract: The aim of this study was to evaluate different conditioning protocols and sonic/ ultrasonic application of an infiltrant resin (IR) in artificial white spot lesions (AWSL). the V/L surfaces of 48 molars were induced to an AWSL and divided in 6 groups, according to the conditioning protocols and application technique: 15% hydrochloric acid (HA) + manual application of the IR; HA + 37% phosphoric acid (PA) + manual application of the IR; HA + ultrasonic application (U) of the IR; HA + sonic application (S) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…In this systematic review, twenty-three articles reported information about microhardness , ten evaluated surface roughness, [27,31,37,47,[49][50][51][52][53][54], sixteen assessed the penetration depth [40,46,50,[55][56][57][58][59][60][61][62][63][64][65][66][67] and eight explored shear bond strength after resin infiltration [32,52,[68][69][70][71][72][73].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this systematic review, twenty-three articles reported information about microhardness , ten evaluated surface roughness, [27,31,37,47,[49][50][51][52][53][54], sixteen assessed the penetration depth [40,46,50,[55][56][57][58][59][60][61][62][63][64][65][66][67] and eight explored shear bond strength after resin infiltration [32,52,[68][69][70][71][72][73].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Overall, twelve studies included bovine teeth (n per group = 803) while twenty-five studies included human teeth (n per group = 865). Nine studies reported data without specimen demineralization previously to resin infiltration [47,54,55,57,59,[61][62][63][64]74] and thirty-nine articles included the demineralization process before the infiltrative resin [21,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][48][49][50][51][52][53]56,58,60,[65][66][67][69][70][71][72][73]. The demineralization process consists of emerging the teeth in a demineralization solution, with pH between 4 and 5 for a period of time that ranges from 1 min to 1200 h, to simulate the formation of WSLs (Table…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…No systematic review or meta-analysis of this subject area was found. All included articles were conducted in Egypt,[ 17 18 19 ] Korea,[ 20 ] USA,[ 18 21 ] Saudi Arabia,[ 22 ] India,[ 23 24 25 26 ] Germany,[ 8 21 , 27 28 29 ] Chile,[ 30 ] Brazil,[ 10 11 , 31 32 ] Romania,[ 33 ] and Switzerland. [ 26 ]…”
Section: R Esultsmentioning
confidence: 99%
“…All the reviewed articles were in vitro , describing a total of 1836 teeth. In 23 studies, 8 studies used natural enamel lesions,[ 8 20 , 21 27 28 29 , 33 34 ] 15 studies created artificial WSLs,[ 10 17 18 19 , 22 23 24 25 26 30 31 32 , 35 36 37 ] and 3 studies used bovine enamel. [ 10 32 , 35 ] To measure the penetration depth, most of the articles used confocal laser scanning microscopies (CLSM) (18 studies),[ 8 10 , 17 18 , 20 21 22 25 , 27 28 29 31 32 33 34 35 36 37 ] followed by polarized light microscopy (one study),[ 23 ] scanning electron microscopy (SEM) (one study),[ 30 ] stereomicroscope (two studies)[ 19 26 ] and optical profilometer (one study).…”
Section: R Esultsmentioning
confidence: 99%
“…The previous preparation with hydrochloric acid to 15% for 120 seconds showed better results in studies that analyzed the different pre-treatments for surfaces to be infiltrated, being recommended by the technique currently used 35 . In addition, the literature suggests that the use of ultrasonic application with the resinous infiltration can increase the depth of the material penetration in the carious lesions 36 .…”
Section: Effect Of Inhibition On the Progression Of The Incipient Carious Lesion: Clinical Studiesmentioning
confidence: 99%